Preoperative use of Granisetron Plus Dexamethasone and Granisetron Alone in Prevention of Post Operative Nausea and Vomiting in Tonsillectomy (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):386-390 The abstract of this article is available on the PubMed website